A New Era of Cardiac Cell Therapy: Opportunities and Challenges. Issue 2 (13th December 2018) - Huang, Ke; Hu, Shiqi; Cheng, Ke
Abstract: Myocardial infarction (MI), caused by coronary heart disease (CHD), remains one of the most common causes of death in the United States. Over the last few decades, scientists have invested considerable resources on the study and development of cell therapies for myocardial regeneration after MI. However, due to a number of limitations, they are not yet readily available for clinical applications. Mounting evidence supports the theory that paracrine products are the main contributors to the regenerative effects attributed to these cell therapies. The next generation of cell‐based MI therapies will identify and isolate cell products and derivatives, integrate them with biocompatible materials and technologies, and use them for the regeneration of damaged myocardial tissue. This review discusses the progress made thus far in pursuit of this new generation of cell therapies. Their fundamental regenerative mechanisms, their potential to combine with other therapeutic products, and their role in shaping new clinical approaches for heart tissue engineering, are addressed. Abstract : This review addresses the opportunities and challenges involved with cardiac regenerative therapies, as well as the new concepts to be learned from biomaterials and bioengineering approaches to drive cell therapies to a new era. This review also summarizes both cellular and noncellular approaches (or the combination of the two) for cardiac regenerative medicine applications.